Superlattice Engineering on 2D Bi2Te3‐Sb2Te3 Chalcogenides - Han Wang; Songqing Zhang; Huijia Luo; Wenwu Pan; Zekai Zhang; Junliang Liu; Yongling Ren; Cailei Yuan; Wen Lei (Advanced Science)
Abstract As a focal point in materials science, 2D superlattices, comprising periodically arranged nanostructures, have emerged as promising platforms for engineering, optoelectronic, and quantum phenomena. In this work, an innovative approach is studied to fabricate multi‐layered 2D Bi2Te3‐Sb2Te3 chalcogenide superlattices including wrapped, lateral and vertical ones. Using a novel precursor switching method, wrapped 2D van der Waals superlattices are synthesized via chemical vapor deposition. Thermal annealing and focused ion beam techniques are employed to achieve both lateral and vertical superlattices with controlled dimensions and sharp interfaces. Comprehensive structural and electronic characterization revealed the high crystalline quality and electronic properties of these superlattices. A comprehensive growth model is also developed to elucidate the growth mechanism and optimize the growth parameters. This research demonstrates a feasible approach to fabricate wrapped, lateral, and vertical superlattices, laying the foundation for further advanced study of their physical properties and potential device applications.